Internationale inspirationer - Seeberg, Lars (Peripeti, 2022)
International inspirations This essay is a personal exposé of the ongoing inspiration between international and Danish theatre, dance and performance during the last 50 years. The author has overseen important Danish festivals, initiated international co-productions and invited outstanding guest performances. Thereby also facilitated Danish artists to go abroad.